Katanin: A Sword Cutting Microtubules for Cellular, Developmental, and Physiological Purposes - Luptovčiak, Ivan; Komis, George; Takáč, Tomáš; Ovečka, Miroslav; Šamaj, Jozef (Frontiers in Plant Science, 2017)
KATANIN is a well-studied microtubule severing protein affecting microtubule organization and dynamic properties in higher plants. By regulating mitotic and cytokinetic and cortical microtubule arrays it is involved in the progression of cell division and cell division plane orientation. KATANIN is also involved in cell elongation and morphogenesis during plant growth. In this way KATANIN plays critical roles in diverse plant developmental processes including the development of pollen, embryo, seed, meristem, root, hypocotyl, cotyledon, leaf, shoot and silique. KATANIN-dependent microtubule regulation seems to be under the control of plant hormones. This minireview provides an overview on available KATANIN mutants and discusses advances in our understanding of KATANIN biological roles in plants.